A Nurse's Perspective on Visual Rehabilitation of Outpatients With Low Vision in China. Issue 1 (January 2020) - Ni, Lingzhi; Li, Keke; Jiang, Longfei; Chen, Jie; Chen, Yanyan; Li, Xiaoman; Lin, Na; Thorn, Frank; Deng, Ruzhi
Abstract: Purpose: The purposes of the study were to analyze patient use and satisfaction with low vision aids (LVAs) at the Wenzhou Medical University Low Vision and Rehabilitation Center and to assess the promotion of visual rehabilitation services as a new responsibility for nurses in China. Methods: Records of 178 patients with low vision (LV) from the Low Vision and Rehabilitation Center examined between October 2015 and October 2016 included basic patient information (e.g., age, diagnosis, visual acuity, educational level) and use of LVAs (patients' own aids, daily duration of LVA use, or refusal to use aids). Results: Sixty percent owned LVAs. Of these, 66% were obtained from a hospital, 26% were obtained from commercial stores, and others were obtained from government or gifts. Patients reported that use of LVAs was reduced because of visual fatigue (39%), inconvenience (22%), and lack of benefit (12%). Reasons for the 40% who had never used visual rehabilitation were nonreferral by doctors (76%), refusal because of inconvenience, discomfort and cosmetics (20%), or a preference for other treatments (4%). Conclusions: Greater awareness of LV rehabilitation by nurses, ophthalmologists, patients, and the public is necessary. Additional government support for LV rehabilitation is also required.